How neighbours influence commercial health insurance purchase: evidence from 2451 rural households in west China. Issue 3 (3rd July 2021) - Han, Kefei; Tan, Jing
ABSTRACT: This paper aims to identify whether neighbors would influence the rural household's decision on commercial health insurance purchase by using a representative sample in west China. We applied an instrumental variable (IV) approach to measure the neighborhood effect, run multiple robustness checks and several heterogeneity analyses. The empirical results find that as neighbors' commercial health insurance purchases increase one unit, the focal family's possibility of purchase would increase by 0.420 units. These results may have some implications for policy-makers to develop the health insurance industry in rural areas more effectively.